An unbelievable ordeal: The experiences of adult survivors treated with extracorporeal membrane oxygenation. Issue 4 (July 2022) - Knudson, Krista A.; Funk, Marjorie; Redeker, Nancy S.; Andrews, Laura K.; Whittemore, Robin; Mangi, Abeel A.; Sadler, Lois S.
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) is a rescue treatment option for adult patients with severe cardiac dysfunction or respiratory failure. While short-term patient outcomes, such as in-hospital mortality and complications, have been widely described, little is known about the illness or recovery experience from the perspectives of survivors. Subjective reports of health are important indicators of the full, long-term impact of critical illness and treatment with ECMO on survivors' lives. Objective: The objective of this study was to describe the experiences and needs of adults treated with ECMO, from onset of illness symptoms through the process of survivorship. Methods: This study was guided by the qualitative method of interpretive description. We conducted in-depth, semistructured interviews with 16 adult survivors of ECMO who were treated at two participating regional ECMO centres in the northeast United States. Additional data were collected from demographic questionnaires, field notes, memos, and medical record review. Development of interview guides and data analysis were informed by the Family Management Style Framework. Qualitative data were analysed using thematic analysis techniques. Results: The sample ( n  = 16) included 75% male participants; ages ranged from 23 to 65 years. Duration from hospital discharge to interviews ranged from 11 to 90 ( M  = 54; standard deviation = 28) months. Survivors progressed through three stages: Trauma and Vulnerability, Resiliency and Recovery, and Survivorship. Participants described short- and long-term impacts of the ECMO experience: all experienced physical challenges, two-thirds had at least one psychological or cognitive difficulty, and 25% were unable to return to work. All were deeply influenced by their own specific contexts, family support, and interactions with healthcare providers. Conclusions: The ECMO experience is traumatic and complex. Recovery requires considerable time, perseverance, and support. Long-term sequelae include impairments in cognitive, mental, emotional, physical, and social health. Survivors could likely benefit from specialised posthospital health services that include integrated, comprehensive follow-up care.